Spinal Cord Electrical Stimulation for Refractory Angina Treatment - Lages, Gustavo Veloso; Oliveira Júnior, Jose Oswaldo (Arquivos Brasileiros de Neurocirurgia: Brazilian Neurosurgery, 2019)
Cardiovascular disease (CVD) is the main cause of death worldwide, including in Brazil. Angina pectoris is a challenging disease because its clinical manifestation is not always related to the degree of obstruction. Visceral pain from any source can be totally disabling. It influences all aspects of the life of a patient and it can be one of the main causes of absence from work and of family disruption. Spinal cord electrical stimulation (SCES) has been traditionally applied for the treatment of neuropathic pain, with good to excellent results. Visceral pain syndrome can be as debilitating and disabling as somatic or neuropathic pain; however, there seems to be a lack of consensus on the appropriate treatment and strategies for these disorders. The major difference of SCES for visceral pain, compared to postlaminectomy syndrome or to regional complex syndrome, is the number of stimulated dermatomes. In most viscera, the somatotopic arrangement has two to four medullar levels, sometimes requiring laterality. After reviewing the literature, we have concluded that SCES is now a viable, low-risk option with satisfactory results for the treatment of neuropathic and visceral pain; therefore, it can be used in refractory angina after the failure of standard therapy. However, further studies are required to increase the application and efficacy of this procedure in the clinical practice.
Keywords: functional neurosurgery; visceral pain; chest angina; angina pectoris; unstable angina; spinal cord electrical stimulation